2015
DOI: 10.1177/1076029615604048
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in Critically Ill Medical Patients Receiving Chemoprophylaxis

Abstract: The rate of VTE in critically ill medical patients remains high despite standard chemoprophylaxis. Obesity is among 8 risk factors independently associated with 90-day VTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Results of the meta-analysis revealed that critically ill patients with COVID-19 have a high prevalence of VTE, despite the use of the present routine prophylactic anticoagulation. In a previous large-scale cross-sectional study that included 11,111 critically ill medical patients who received chemoprophylaxis, the overall prevalence of VTE was 6.5% ( 40 ), which is significantly lower than that in critically ill patients with COVID-19 found in the meta-analysis (28.4%). In a previous meta-analysis, critically ill patients were admitted in the ICU, and the mean prevalence of DVT was reported to be 12.7% ( 14 ), which was considerably lower than that for the critically ill patients with COVID-19 found in the present meta-analysis (25.6%).…”
Section: Discussionmentioning
confidence: 72%
“…Results of the meta-analysis revealed that critically ill patients with COVID-19 have a high prevalence of VTE, despite the use of the present routine prophylactic anticoagulation. In a previous large-scale cross-sectional study that included 11,111 critically ill medical patients who received chemoprophylaxis, the overall prevalence of VTE was 6.5% ( 40 ), which is significantly lower than that in critically ill patients with COVID-19 found in the meta-analysis (28.4%). In a previous meta-analysis, critically ill patients were admitted in the ICU, and the mean prevalence of DVT was reported to be 12.7% ( 14 ), which was considerably lower than that for the critically ill patients with COVID-19 found in the present meta-analysis (25.6%).…”
Section: Discussionmentioning
confidence: 72%
“…central venous access), the use of vasopressors and other medications, blood product transfusion, mechanical ventilation, and certain acquired thrombophilias. 41,42 While this glimpse of evidence may partially support the use of therapeutic-dose anticoagulants in patients with these specific conditions, 12,13 2 main factors must be taken into consideration before implementing such treatment in clinical practice. Firstly, it is possible that only particular subgroups of criticallyill patients with certain risk factors could benefit from therapeutic-dose anticoagulation, as Klok et al reported no mortality benefits among those receiving therapeutic-dose anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…central venous access), the use of vasopressors and other medications, blood product transfusion, mechanical ventilation, and certain acquired thrombophilias. 41,42…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in critically ill, non-critically ill, and patients with sepsis support this association. 18,39,40 In patients with sepsis and critically ill medical patients receiving thromboprophylaxis, CVC increased the risk of VTE by an OR of 2.82 (95% CI 1.07-7.38) and 2.64 (95% CI 1.87-3.72), respectively. 18,39 Central venous catheter–related thrombosis is an important complication of CVC insertion 41 and a risk factor for upper extremity DVT.…”
Section: Discussionmentioning
confidence: 99%